Analisis Pengaruh Kualitas Pelayanan Terhadap Loyalitas Nasabah Baitul Maal wat Tamwil - Rini Dwiyani Hadiwidjaja (Department of Accounting-Faculty of Economic and Business (FEB), 2017)
The aim of this research is to analyze the effect of service quality to customers’ loyalty in BMT customers. The method that used in this research is descriptive analysis and multiple regression analysis. The result shows that the service quality in good and high category. But, the customers’ loyalty in medium category. To increase the loyalty of the customers, it needs to increase the service quality to the customers. This will had a positive effect on customers loyalti. Customers’ loyalty can be a good promotion to the BMT.